Peningkatan Kapasitas SDM di RSJ. HB. Saanin dalam Pengolahan Data Kesehatan Menggunakan Pivot Table dan Dashboard Ms Excel - Mardi, Yuli; Nila Mayasari; Vanya Putri Ramadhani (CV. Ulil Albab Corp, 2025)
HB Saanin Psychiatric Hospital faces challenges in health data management that is still conducted manually, limiting efficiency and accuracy in decision-making. A major constraint lies in the limited understanding of healthcare professionals and administrative staff regarding data analysis tools, such as Pivot Tables and Dashboards in Microsoft Excel. To address this issue, this Community Service Program (PKM) aimed to enhance the capacity of human resources at HB Saanin Hospital in health data processing through training and mentoring on Excel features. The program consisted of preparation, training implementation, evaluation, and mentoring stages. The training focused on two key aspects: (1) data analysis using Pivot Tables for faster and more accurate information presentation, and (2) the development of interactive Dashboards as data visualization tools to support evidence-based decision-making. Evaluation was carried out through pre-tests and post-tests, as well as direct observation of participants’ application in their workplace. Results showed an increase in participants’ understanding, with an average pre-test score of 73.64 compared to a post-test score of 85. The outcomes indicate improved skills of healthcare staff in efficient data management and analysis, thereby supporting service optimization at HB Saanin Hospital through Excel-based information technology.